A Cognitive Linguistic Study of the English Preposition 'in' (Journal of the College of Education for Women, 2019)
The present study aims at analyzing the polysemy of the English preposition in from the cognitive linguistic (CL) point of view using Evans' and Tyler's approach (2003). The perplexity faced by Iraqi second language learners (L2) due to the multi-usages of this preposition has motivated the researcher to conduct this study. Seventy-six second year university students participated in this experimental study. The data of the pre-test and post-test were analyzed by SPSS statistical editor. The results have shown the following: First, a progress of more than (0.05≤) has been detected as far as students' understanding of the multiple usages of the preposition in is concerned. Second, the results of the questionnaire have shown a prominent positive change in the students' attitude toward CL approach. Third, the main source of difficulty has been shown to be attributed to the diversity in the semantics of the preposition in. Fourth, CL as an approach has proven its effectiveness in accurately comprehending the semantics of the English preposition in.